At several points in the network: territorial division of Contact Center Operations in Brazil - Almeida, Marina Castro (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2014)
The present article intents to analyze the appropriation of Brazilian uneven geographical development by Contact Center’s companies. The constitution of the Brazilian telemarketing resulted from outsourcing of services, as a strategy to decrease labor costs. The privatization of the telecommunications companies, in the late 1990s, caused the expansion of operations provided by transnational corporations. The corporation’s territorial division of labor are examined to discuss the distribution and accumulation of surplus, starting from a political economy of the territory. The centripetal and centrifugal forces that drive the movement of operations and territorial incentives granted to companies are also analyzed. Among the main corporate strategies, are the concentration of control in the main Brazilian cities and the dispersion of production units for the urban non-metropolitan and for the Northeast. The selective use of technical and informational density allows companies to lucrative incorporate areas where resources, especially labor and capital, are devalued.